The Assessment of Students’ English Writing Skill at SMA Yaspen Tugu Ibu Depok - Mulyadi Mulyadi; Siti Nurani; Nurul Frijuniarsi (Scope : Journal of English Language Teaching, 2020)
The aim of this research is to analyze empirically English writing skill of Senior High School students. This research is a descriptive qualitative research. The population of this research is the second grade students from SMA Yaspen Tugu Ibu in Depok. The sample was taken through simple random sampling of which 25 students as samples of this research. For collecting the data, the instruments used in this research were writing test and interview. The writing test was conducted to obtain the writing skill indicators, while the interview was carried out to elicit information of students’ problems in writing. The result of this research explained that students’ English writing skill was definitely good at SMA Yaspen Tugu Ibu Depok. There were 88% of students with scores more than 50 and only 12 % with scores less than 50. In conclusion, the students’ writing skill at SMA Yaspen Tugu Ibu is considered to be high category in English writing skill.